The Rise and Fall of the Neoliberal Order: America and the World in the Free Market Era - Kuziemko, Ilyana; Naidu, Suresh (Journal of Economic Literature, 2024)
Ilyana Kuziemko of Princeton University and Suresh Naidu of Columbia University review “The Rise and Fall of the Neoliberal Order: America and the World in the Free Market Era” by Gary Gerstle. The Econlit abstract of this book begins: “Examines the history of the political order that took shape under Ronald Reagan and achieved dominance under Bill Clinton in the 1990s and early 2000s, highlighting the sharp distinction of this political order from those that preceded it.”